Analisis Yuridis Terhadap Undang-Undang Nomor 6 Tahun 2023 Tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 Tentang Cipta Kerja - Hariadi, David; Hesti Wulan; Sonya Claudia Siwu (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Constitutional Court Decision Number 91/PUU-XVIII-2020 states that Law Number 11 of 2020 concerning Job Creation is conditionally unconstitutional. This is the basis for the government to take action by establishing Government Regulation in Lieu of Law Number 2 of 2022 to replace Law Number 11 of 2020. However, the action taken by the government has drawn a lot of criticism from the public because the government is considered not careful and too hasty in taking action by establishing government regulations in lieu of the law. Consider whether the government takes appropriate action by looking comprehensively at the presence or absence of force crunch which is the basis for the establishment of government regulations in lieu of law in accordance with Article 22 Paragraph (1) of the 1945 Constitution.